High-temperature molecular beam epitaxy of hexagonal boron nitride with high active nitrogen fluxes - Cheng, Tin S.; Summerfield, Alex; Mellor, Christopher J.; Khlobystov, Andrei N.; Eaves, Laurence; Foxon, C. Thomas; Beton, Peter H.; Novikov, Sergei V. (MDPI, 2018)
Hexagonal boron nitride (hBN) has attracted much attention as a key component in van der Waals heterostructures and as a wide band gap material for deep-ultraviolet devices. We have recently demonstrated plasma-assisted molecular beam epitaxy (PA-MBE) of hBN layers on substrates of highly oriented pyrolytic graphite at high substrate temperatures of ~1400 oC. The current paper will present data on the high-temperature PA-MBE growth of hBN layers using a high-efficiency RF nitrogen plasma source. Despite the more than 3-fold increase in nitrogen flux with this new source, we saw no significant increase in the growth rates of the hBN layers, indicating that the growth rate of hBN layers is controlled by the boron arrival rate. The hBN thickness increases to ~90 nm with decrease in the growth temperature to 1080 oC. However, the decrease in the MBE temperature led to a deterioration of the optical properties of the hBN. The optical absorption data indicate that an increase in the active nitrogen flux during the MBE process improves the optical properties of hBN and suppresses defect related optical absorption in the energy range 5.0-5.5 eV.